2018
DOI: 10.1007/s11469-018-9938-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self/Everyday Creativity and Depression on the Relationship Between Creative Personality Traits and Problematic Social Media Use Among Emerging Adults

Abstract: Personality is one of the important contributory factors in the development of problematic technology use. The purpose of the present study was to investigate the direct and indirect associations of creative personality traits with problematic social media use via self/everyday creativity, depression, and loneliness. A total of 460 Turkish emerging adults aged between 18 and 26 years (61% female) were surveyed. Findings indicated that (i) taskorientedness was indirectly associated with problematic social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Negative affect (depression, anxiety, social media communication apprehension, rumination). Out of 10 studies, all reported negative affectivity as a potential risk factor for PSMU (Dempsey et al, 2019 ; Gao et al, 2021 ; Hong et al, 2014 ; Hou et al, 2019 ; Jasso-Medrano & Lopez-Rosales, 2018 ; Kircaburun et al, 2020b ; Punyanunt-Carter et al, 2018 ; Sayeed et al, 2020 ; Xie & Karan, 2019 ). Nine showed a small effect size (90%) and one a mixed one (10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative affect (depression, anxiety, social media communication apprehension, rumination). Out of 10 studies, all reported negative affectivity as a potential risk factor for PSMU (Dempsey et al, 2019 ; Gao et al, 2021 ; Hong et al, 2014 ; Hou et al, 2019 ; Jasso-Medrano & Lopez-Rosales, 2018 ; Kircaburun et al, 2020b ; Punyanunt-Carter et al, 2018 ; Sayeed et al, 2020 ; Xie & Karan, 2019 ). Nine showed a small effect size (90%) and one a mixed one (10%).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the studies found depression (Gao et al, 2021 ; Hong et al, 2014 ; Hou et al, 2019 ; Jasso-Medrano & Lopez-Rosales, 2018 ; Kircaburun et al, 2020b ; Sayeed et al, 2020 ), anxiety (Gao et al, 2021 ; Hou et al, 2019 ; Xie & Karan, 2019 ), perceived stress (Hou et al, 2017b ), Social media Communication Apprehension (Punyanunt-Carter et al, 2018 ) and rumination (Dempsey et al, 2019 ) to be risk factors. In addition, Jasso-Medrano and Lopez-Rosales ( 2018 ) found a significant and negative effect of suicidal ideation on PSMU.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of status conflict is just above the .60, which is acceptable and sufficient to draw the conclusion (Taber, 2018;van Griethuijsen et al, 2015). Studies in organizational psychology domain, with alpha values ranging between .60 and .69, have been published in reputed journals and are well-cited (e.g., Kircaburun et al, 2020;Lehman & Simpson, 1992;Mayer & Davis, 1999;Spector et al, 2006). In the second step we compared hypothesized model with other four alternate models to see the fit between the data and hypothesized model.…”
Section: Reliability Correlations and Confirmatory Factor Analysismentioning
confidence: 99%
“…In order to explain why some people engage in technology usage and why it sometimes further develops into problematic behavior, we make us of the Interaction of Person -Affect -Cognition -Execution (I-PACE) model of behavioral addictions (Brand et al, 2019). I-PACE was originally developed as a framework to understand the development and maintenance processes of specific internet-use addictions (Brand et al, 2016), but due to the similarities with problematic usage patterns of technologies, it has been extended to research on problematic social media use (Kircaburun et al, 2020) and problematic use of smartphones as well (Duke & Montag, 2017) such that nowadays the model is being used in the context of a wide range of modern technologies (Brand et al, 2019).…”
Section: The Relation Between the Key Constructs The I-pace Modelmentioning
confidence: 99%